Pottery Production in the Buddhist Communities in Central Asia: The Kushan‐Sassanian Pottery Workshop of Kara Tepe (Termez, Uzbekistan). (19th May 2015) - Tsantini, E.; Martínez Ferreras, V.; Ariño Gil, E.; Gurt I Esparraguera, J. M.; Pidaev, S.
Abstract : We present the first full archaeometrical study of Kushan‐Sassanian pottery from the Buddhist monastic complexes at Kara Tepe (Termez, Uzbekistan), recovered both in the pottery workshop and in the monastery, using a combination of analytical methods (XRF, XRD, SEM–EDS and OM). The study allowed the identification of the reference group, the correspondent fabric, the raw materials used for its productions, some of the technological processes involved in manufacture and several weathering processes. All the results confirm that the kiln was supplying the religious community of the monastery with pottery, made using local raw materials, and highlight the possibility that the kiln could have supplied the nearby monastic complexes, where no kilns have been found. Further archaeological evidence indicates the existence of specialized potters working itinerantly at the broader Bactrian area.